(untitled) (Politeja, 2015)
Social‑Political Development of Transcarpatia The author of the article has analyzed the social‑political development of Transcarpathia and the factors conditioning it. The author has performed the periodization of the mentioned development on the basis of criteria of dominance/conflict of political elites in the region. Four periods have been distinguished: the first − 1991‑2004 − the period of formation of the local authority and dominance of Social Democratic Party of Ukraine (united) in it; the second − 2004‑2010 − the structuring of political space in the oblast after the 2004 presidential election; the third − starting from 2010 − changes in the structure of power relations in Transcarpathia after the presidential elections in 2010; the fourth − starting from 2014 − formation of a new system of government after the Ukrainian Revolution (December 2013 − February 2014). Much attention has been paid to the electoral process in the region, as election results have an impact on politics and society of the region. The parliamentary, presidential and local elections have been considered as well as their impact on social and political development of the region. Regional specificity of social and political development of Transcarpathia has been consditioned by the following factors: geographical location of the region (border proximity with European Union countries): historical background (participation in elections by party lists to the parliament of Czechoslovakia in 1924, 1925, 1929, 1935, declaration in 1939 of independent state − Carpathian Ukraine and participation in the elections to Soym); social – demographic characteristics of the electorate: the specifics of the formation of regional political elites (dependent on Kyiv); features of the formation and development of the party structure of the region.